The role of email in improving task performance among the executives in Malaysia. - Baninajarian, Narges; Abdullah, Zulhamri; Bolong, Jusang (New South Wales Research Centre Australia (NSWRCA), 2011)
As new technologies that support managerial communication became widely used, the question of how they influence task performance increases in importance. This study aims to examine the role of email in improving task performance. Specifically, this study attempts to look at how email richness and ease of use can affect task performance. The results of this study revealed that the executives experienced moderate to high level of task performance while using email. The results also showed that the executives perceived email in moderate to high level in richness while they perceived email as an easy to use communication medium. Perceived email richness and perceived email ease of use had a positively significant relationship with task performance. However, the positive correlation coefficient values indicated that the in crease in email richness and ease of use perception generates an increase in task performance.